Analisis Penerapan PSAK No.16 Dalam Perlakuan Akuntansi Aset Tetap Perusahaan - Mayangsari, Anisa Putri; Nurjanah, Yayuk (Institut Bisnis dan Informatika Kesatuan, 2018)
Increased growth and development are the company's top priorities. However, maintaining and developing the company is not easy. Many important factors must be considered to run the company well, including organizational factors, personnel, and others. The survival and success of the company will be determined by the speed of reaction and the accuracy of the strategies taken by the company leaders as well as the support of all members of the organization. In a company, there are always fixed assets to carry out its operations. Assets still have an important position in the company because they require large amounts of funds and are embedded in a long period of time. The purpose of this research is to find out how the recognition, measurement and disclosure of fixed assets at CV Bangun Perkasa Furniture (BPF). To find out how to recognize, measure and disclose fixed assets in accordance with PSAK No. 16 on CV Bangun Perkasa Furniture (BPF). The results of the Analysis of Accounting for Intangible Fixed Asset (PSAK No.16) (Case study on CV. Bangun Perkasa Furniture) there are some results that the recognition of Bangun Perkasa Furniture is not appropriate not in accordance with PSAK 16 because the acquisition value only recognizes the principal value of the asset and in its disclosure the company does not apply the basic basis in accordance with PSAK 16. This is very different from that stated in PSAK 16. In measuring the fixed assets that are in CV. Bangun Perkasa Furniture in accordance with PSAK 16. Keywords : PSAK 16, fixed assets, financial statement